Traditional leaders and governance in Micronesia - Haglegam, John (Canberra, ACT: State, Society and Governance in Melanesia (SSGM) Program, The Australian National University, 1998)
Let me assert from the outset that contemporary politics and governance in Micronesia are influenced to a large extent by the traditional system which underlies the modern system. This traditional system has given a unique Micronesian flavour to contemporary politics and governance, albeit undemocratic in some cases. With careful nurturing through regular briefings and consultation by government leaders, the traditional chiefs can be relied upon to muster the necessary public support for policy implementation. The customary power of the traditional chiefs in Micronesia varied from culture to culture. For instance, on Kosrae the power was centralised in a very powerful ruler, while on Yap, the power of the chiefs was decentralised and subjected to elaborate checks and balances built into the customary political relationship. In Palau, the power was vested in the heads of two alliances of villages. These alliances were involved in constant fighting for domination. In Chuuk, the most powerful traditional leaders were the village chiefs. In the Marshall Islands, the most powerful leaders were the two paramount chiefs, one heading each of the two island chains—the Ratak and Ralik. Surprisingly, for low island chiefs, these two paramount chiefs had absolute power. In Pohnpei, the power of the traditional leaders was exercised by a paramount chief in each of the five kingdoms. However, the exercise of their customary power is checked by the head of a chiefly parallel line whose relationship to the paramount chief is like a father-son relationship, the paramount chief being the father. In the outer islands of Chuuk and Yap, each island had its paramount chief. In spite of the varied power of the traditional chiefs in Micronesia, almost all of them inherit their position through their mother. In Palau, the senior women in the chiefly clan select the paramount chief. Yap is the exception to this general rule. Both the age of the mother and her son were important determining factors for the leadership position in all Micronesian societies. Quite often a young man who had customary claim to a leadership position would be bypassed in favour of an older man. When this happened, usually the older man served in that position until death, then the rightful holder of the title could assert his right. The exercise of customary chiefly power was the domain of men. In a few cases, women would become chiefs, but the effective power would be exercised by men.